Healing of Planar Defects in 2D Materials via Grain Boundary Sliding. Issue 16 (27th February 2019) - Zhao, Xiaoxu; Ji, Yujin; Chen, Jianyi; Fu, Wei; Dan, Jiadong; Liu, Yuanyue; Pennycook, Stephen J.; Zhou, Wu; Loh, Kian Ping
Abstract: Understanding the mechanisms and kinetics of defect annihilations, particularly at the atomic scale, is important for the preparation of high‐quality crystals for realizing the full potential of 2D transition metal dichalcogenides (TMDCs) in electronics and quantum photonics. Herein, by performing in situ annealing experiments in an atomic resolution scanning transmission electron microscope, it is found that stacking faults and rotational disorders in multilayered 2D crystals can be healed by grain boundary (GB) sliding, which works like a "wiper blade" to correct all metastable phases into thermodynamically stable phases along its trace. The driving force for GB sliding is the gain in interlayer binding energy as the more stable phase grows at the expanse of the metastable ones. Density functional theory calculations show that the correction of 2D stacking faults is triggered by the ejection of Mo atoms in mirror twin boundaries, followed by the collective migrations of 1D GB. The study highlights the role of the often‐neglected interlayer interactions for defect repair in 2D materials and shows that exploiting these interactions has significant potential for obtaining large‐scale defect‐free 2D films. Abstract : It is found that 2D planar defects in multilayered 2D crystals can be healed by grain boundary (GB) sliding, which works like a "wiper blade" to correct all metastable phases into thermodynamically stable phases along its trace. The driving force for GB sliding is the gain in interlayer binding energy. The study highlights the role of the often‐neglected interlayer interactions for defect repair, which have significant potential for obtaining large‐scale defect‐free 2D films.